Prevalence and risk factors of needlestick injuries, sharps injuries, and blood and body fluid exposures among operating room nurses in Thailand - Nongyao Kasatpibal (2018)
© 2016 Association for Professionals in Infection Control and Epidemiology, Inc. Background Operating room nurses are at high risk for occupational exposure to bloodborne pathogens. This study examined the prevalence of and risk factors for needlestick injuries (NSIs), sharps injuries (SIs), and blood and body fluid exposures (BBFEs) among operating room nurses in Thai hospitals. Methods A cross-sectional study was performed in 247 Thai hospitals. Questionnaires eliciting demographic data and information on injury occurrence and risk factors were distributed to 2500 operating room nurses, and 2031 usable questionnaires were returned, for a response rate of 81.2%. Adjusted odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using multiple logistic regression analysis. Results The prevalence of NSIs, SIs, and BBFEs was 23.7%, 9.8%, and 40.0%, respectively. Risk factors for NSIs were training without practice (OR, 1.67; 95% CI, 1.29-2.17), haste (OR, 4.81; 95% CI, 3.41-6.79), lack of awareness (OR, 1.36; 95% CI, 1.04-1.77), inadequate staffing (OR, 1.60; 95% CI, 1.21-2.11), and outdated guidelines (OR, 1.69; 95% CI, 1.04-2.74). One risk factor was identified for SIs: haste (OR, 2.43; 95% CI, 1.57-3.76). Risk factors for BBFEs were long working hours per week (OR, 2.07; 95% CI, 1.06-4.04), training without practice (OR, 1.55; 95% CI, 1.25-1.91), haste (OR, 1.66; 95% CI, 1.30-2.13), lack of awareness (OR, 1.54; 95% CI, 1.22-1.95), not wearing protective equipment (OR, 1.61; 95% CI, 1.26-2.06), and inadequate staffing (OR, 1.63; 95% CI, 1.26-2.11). Conclusion This study highlights the high prevalence of NSIs, SIs, and BBFEs among Thai operating room nurses. Preventable risk factors were identified. Appropriate guidelines, adequate staffing, proper training, and self-awareness may reduce these occurrences.